Conservation Planning in an Era of Change: State of the U.S. Prairie Pothole Region. (14th May 2013) - Doherty, Kevin E.; Ryba, Adam J.; Stemler, Casey L.; Niemuth, Neal D.; Meeks, William A.
Abstract We assessed attainability of landscape‐level conservation planning goals in the United States portion of the Prairie Pothole Region by summarizing and analyzing data on status, trends, and potential future of grasslands and wetlands. All published literature and new data analyses consistently indicate declines in grassland and wetland area. When we incorporated time as a conservation planning metric, the importance of seemingly small wetland (0.05–0.57%) and grassland (0.4–1.3%) annual loss rates became apparent. Moreover, we highlighted large differences in the amount of future grassland (30–67%) and wetland (47–93%) resulting from seemingly small changes in loss percentages. Our analyses clearly demonstrate that time, along with current status and trends of target habitat(s), must be incorporated when setting habitat conservation goals, otherwise goals may be unrealistic. Prairie Pothole Joint Venture (PPJV) partners protected an average of 0.20% of the 3.3 million ha extant wetlands and 0.26% of the 10.7 million ha extant grasslands/year. Consequently, PPJV partners cannot reach stated conservation goals given current habitat loss rates unless 1) increased funding is secured for land conservation, 2) landowner interest and acceptance of conservation programs remains high, and 3) wetland and grassland loss rates are decreased via public policy, particularly through agriculture programs, or other mechanisms. Otherwise, PPJV habitat conservation goals, and ultimately species population goals, will need to be reduced accordingly. Our comprehensive assessment may help the PPJV and other landscape‐level planning efforts discriminate between goals they would like to attain versus goals they are likely to achieve. © 2013 The Wildlife Society.